(untitled) (Lapai Journal of Economics, 2023)
This study evaluated the effects of safety culture metrics on risk scorecard among manufacturing firms in Lagos State. The study employed a descriptive survey research design; cum multiphase sampling techniques comprised of judgmental and convenience. Thus, a structured questionnaire of two hundred and eighty-two (282) were gathered from selected manufacturing firms in Lagos State. The statistical techniques adopted were simple frequency percentage, Friedman rank test, and simple regression method. While rank order tests were conducted for both safety culture and risk score metrics, positively low relationship was established between safety culture and risk scorecard among selected manufacturing firms in Lagos State. On recommendations, firms should endeavour to scale and underwrite in promoting vigorous safety cultures that permit for safety performance. The integration of safety culture and risk scorecard metrics should be yearned for to enhance organisational capabilities and ensure survival. Ensuring safety participation, priority, control, engagement, and communication will help organisation in building robust capacities to advance operational efficiency and quality.